21st-Century Islamic Religious Education Pedagogical Innovation: Balancing Technology, Active Learning Models, and Character Strengthening - Muhammad Rifkhi Maulana; Muflikhatun Muflikhatun; Chairul Anwar; Syaiful Anwar; Muhammad Idris (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Pedagogical innovation in Islamic Religious Education (PAI) is inevitable amidst the challenges of globalization and the industrial revolution 4.0. This study aims to analyze the forms of 21st-century PAI pedagogical innovation, its implementation in educational institutions, and its impact on strengthening students' character. The research employs a qualitative approach with library research. Data analysis techniques use the Miles & Huberman model through data reduction, display, and conclusion drawing. The results indicate that PAI pedagogical innovations encompass three main pillars: integration of digital technology (e-learning, AI, multimedia), application of active learning models (Active Learning, PjBL, Discovery Learning), and contextual approaches linking material with students' social realities. The impact of these innovations is proven significant in improving learning quality (cognitive, affective, psychomotor) and strengthening religious character such as honesty, responsibility, tolerance, and spirituality. Optimal implementation requires synergistic support from the teacher's role as innovator, holistic curriculum integration, adequate infrastructure, and a conducive learning environment. This study recommends strengthening teachers' digital literacy and sustainable policies from educational institutions to maximize the potential of pedagogical innovation in shaping morally noble and globally competitive generations.